2020
DOI: 10.1111/j.1600-0390.2020.12223.x
|View full text |Cite
|
Sign up to set email alerts
|

Fishers of The Corded Ware Culture in The Eastern Baltic

Abstract: Between 2800 and 2400 cal BC pastoralists from Central Europe migrated into the eastern Baltic paving the way for the Corded Ware Culture (CWC), and a new type of economy, animal husbandry. Traditionally the CWC people were viewed as highly mobile due to the lack of substantial traces of dwellings and material culture at settlement sites; they were reliant on an economy based on animal husbandry as demonstrated by zooarchaeological and stable isotopic evidence. However, this paradigm is beginning to shift. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…This was identified in the Mesolithic, Subneolithic and Neolithic individuals, and perhaps some of the Bronze Age individuals. This finding fits well with the mixed-type economy recently proposed for the southeastern Baltic population during the Neolithic and the Early Bronze periods, based on carbon and nitrogen stable isotope data, organic residue analysis of ceramic vessels, and recent macrobotanical analyses (Piličiauskas et al 2017a(Piličiauskas et al , 2020(Piličiauskas et al , 2021Robson et al 2019). It seems that mobile stockbreeding and extensive barley farming were supplemented by the continued exploitation of wild resources for some time.…”
Section: Mobility Patternssupporting
confidence: 89%
See 1 more Smart Citation
“…This was identified in the Mesolithic, Subneolithic and Neolithic individuals, and perhaps some of the Bronze Age individuals. This finding fits well with the mixed-type economy recently proposed for the southeastern Baltic population during the Neolithic and the Early Bronze periods, based on carbon and nitrogen stable isotope data, organic residue analysis of ceramic vessels, and recent macrobotanical analyses (Piličiauskas et al 2017a(Piličiauskas et al , 2020(Piličiauskas et al , 2021Robson et al 2019). It seems that mobile stockbreeding and extensive barley farming were supplemented by the continued exploitation of wild resources for some time.…”
Section: Mobility Patternssupporting
confidence: 89%
“…3200 to 2800 cal BC (Piličiauskas 2018;Rimantienė 1989Rimantienė , 2002. Simultaneously, animal husbandry was incorporated into a mixed type of economy in which wild resources continued to be exploited alongside domesticated species (Piličiauskas et al 2020;Robson et al 2019). At ca.…”
Section: Introductionmentioning
confidence: 99%
“…This dataset is further supplemented by 15 Porous and six Lubāna-type ceramic samples from Latvia, resulting in a total of 199 samples, of which 113 are reported here for the first time. The biomarker and isotope results of ORA from all samples are reported in electronic supplementary material, table S6, whereas the results from previous publications [ 25 , 63 , 64 ] were included in the dataset only if both biomarker and compound specific isotope data was available.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, the biological legacy and the aftermath of the arrival of early farming in the east Baltic, set in the context of local forager communities, northern climatic conditions with dense woodland and aquatic landscapes, abundant wild resources and missing indigenous species suitable for domestication, has remained ambiguous. Recent biomolecular findings have confirmed that the introduction of new, domesticated species took place from the 3rd millennium cal BCE onwards [6,[24][25][26], but we lack clarity concerning the extent and character that the subsistence and gross diet actually changed and for whom.…”
Section: Introductionmentioning
confidence: 97%